Intracochlear Pressure Changes After Cochlea Implant Electrode Pullback—Reduction of Intracochlear Trauma. Issue 4 (11th July 2019) - Lauer, Gina; Uçta, Julica; Decker, Lars; Ernst, Arneborg; Mittmann, Philipp
Abstract : Objective: Different aspects should be considered to achieve an atraumatic insertion of cochlear implant electrode arrays as an important surgical goal. Intracochlear pressure changes are known to influence the preservation of residual hearing. By using the intraoperative "pullback technique, " an electrode position closer to the modiolus can be achieved than without the pullback. The aim of the present study was therefore to investigate to what extent the pullback technique can influence intracochlear pressure changes. Methods: Insertions of cochlear implant electrodes were performed in an artificial cochlear model with two different perimodiolar arrays. Intracochlear pressure changes were recorded with a micro‐optical pressure sensor positioned in the apical part of the cochlear. After complete insertion of the electrode array, a so‐called pullback of the electrode was performed. Results: Statistically significant pressure differences were measured if the electrode array was wet (ie, moisturized) during the pullback. Relative pressure changes in electrodes with smaller total volume are lower than pressure changes in larger electrodes. Conclusion: The preservation of residual hearing and, thus, the resulting postoperative audiological outcome has a major impact on the quality of life of the patients and has become of utmost importance. Intracochlear pressure changes during the pullback manoeuver are small in absolute terms, but can even be still reduced statistically significantly by a moistening the electrode before insertion. Using the pullback technique in cases with residual hearing does not affect the probability of preservation of residual hearing but could lead to a better audiological outcome. Level of Evidence: NA